Tata fasilitas rekreasi tepi sungai: studi kasus kawasan wisata Sungai Bindu, Kesiman, Denpasar - Adi Saputra, I Putu Sadewa; Mayadewi, Ni Nyoman Ari; Semarajaya, Cokorda Gede Alit (Jurnal Arsitektur Lansekap; Vol.6, No.1, April 2020DO - 10.24843/JAL.2020.v06.i01.p07, 2020)
Denpasar City is the capital of Bali Province which has a strategic location. Denpasar City is also famous for its cities which have many rivers. Bindu River as a place of recreation is one of the alternative outdoor recreation in Denpasar City. Bindu River has various facilities that can be used by visitors as a place of recreation. The facilities Bindu River area is still not in accordance with good standardization and placement that is not good. This study aims to maximize existing facilities by providing recommendations for facilities that are referenced through good standards and laying. The research method used is the survey method with observation techniques, interviews, documentation, questionnaires, and literature studies. The results of the study state that there are several facilities that have not followed good standardization and laying. Facilities available in the Bindu River area are: seating, trash cans, garden lights, toilets, culinary stands, gazebos, jogging tracks as well as recreational facilities such as mini soccer fields, physical games, tubing, sports equipment, and gymnastics area. Many visitor activities are carried out in the Bindu River area, but some of the facilities provided are in poor condition. The efforts made to improve the quality of facilities are by following the standards in the Time-Saver Standards for Landscape Architecture.